BUDAYA ORGANISASI DAN INOVASI PELAYANAN TERHADAP EFEKTIFITAS PELAYANAN DI MALL PELAYANAN PUBLIK KABUPATEN MAROS - Sukawati, Herlina; Widyawati, Widyawati; Sulmiah, Sulmiah (Jurnal Administrasi Negara, 2024)
The presence of a public service mall as a regional government step in creating a new service system and adapting to community demands has not been completely successful in providing quality services to the community. The fear of failure, lack of incentive to innovate, lack of employee development and learning in improving performance, as well as lack of employee understanding of service programs, are the main problems in providing services at the Public Service Mall. This problem is indicated to occur in the organizational aspect, so this research was conducted to determine the influence of organizational culture and public service innovation on the effectiveness of public services at the Maros Regency public service mall. So that researchers can easily find the magnitude of the influence of organizational culture and service innovation on the effectiveness of public services, quantitative research methods are used. The sample in this study amounted to 98 people. Data sourced from distributing questionnaires was analyzed using the SmartPLS 4.0 application. The results of the analysis show that the effectiveness of public services at the Maros Regency Public Service Mall is predominantly influenced by Organizational Culture. The influence given is 14.9%. Public Service Innovation does not have an impact on increasing service effectiveness at the Maros Regency public service mall. Taken together, organizational culture and service innovation do not affect the effectiveness of public services. As the dominant variable in the research, organizational culture also influences the implementation of service innovation in Maros Regency public service malls by 41.6%. The Maros Regency Government, in maximizing the role of the Public Service Mall in improving the quality of public services, needs to maximize strategic innovation and governance innovation, because a strong organizational culture also needs to be supported by achievement and management strategies, to achieve the mission of increasing the effectiveness of public services in Maros Regency.